Seleksi Galur Generasi F4 Padi Beras Merah Tahan Rebah: Seleksi Galur Generasi F4 Padi Beras Merah Tahan Rebah - Eries Dyah Mustikarini; Gigih Ibnu Prayoga; Bama Aprilian (Universitas Bangka Belitung, 2020)
Lodging of the paddy plants causes a decrease in rice plant production. Lodging resistants rice plants can be produced through plant breeding. The purpose of the research is selection lodging resistant F4 lines. The research was carried out from December 2018 to May 2019 in the ultisol field, Bangka Regency, Bangka Belitung Province. The F4 lines were planted by a single plant design. Plants were selected using the pedigree method. The result showed that the characteristics of rice F4 lines from crossed were less than 90 cm of height and 70 selected F4 lines seemed to have lodging resistance based on the plant height character and also supported by stem diameter, panicle height, stem strength, and pithy seeds weight per clump.